2020
DOI: 10.1111/tbed.13458
|View full text |Cite
|
Sign up to set email alerts
|

Theileria annulatasurface protein (TaSP) is a target of cyclin‐dependent kinase 1 phosphorylation in Theileria annulata‐infected cells

Abstract: Leucoproliferative Theileria parasites possess the unique capability to transform their bovine host cell, resulting in tumour‐like characteristics like uncontrolled proliferation. The molecular mechanisms underlying this parasite‐dependent process are only poorly understood. In the current study, bioinformatic analysis of the Theileria annulata surface protein (TaSP) from different T. annulata isolates identified a conserved CDK1 phosphorylation motif T131PTK within the extracellular, polymorphic domain of TaS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Therefore, investigating the interactions of T. annulata and its host provides insights into T. annulata -induced pathogenesis. Although some molecules have been reported to affect T. annulata -induced transformation, metabolism, and invasion by regulating host signaling-hubs [ 8 10 , 21 ], the evidence for the relevant roles of secreted multifamily (SVSP)-host interactions has not been presented until now. Herein, SVSP454, a member of the SVSP multigene family, was used as bait to explore its interacting molecules in host cells.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, investigating the interactions of T. annulata and its host provides insights into T. annulata -induced pathogenesis. Although some molecules have been reported to affect T. annulata -induced transformation, metabolism, and invasion by regulating host signaling-hubs [ 8 10 , 21 ], the evidence for the relevant roles of secreted multifamily (SVSP)-host interactions has not been presented until now. Herein, SVSP454, a member of the SVSP multigene family, was used as bait to explore its interacting molecules in host cells.…”
Section: Resultsmentioning
confidence: 99%
“…In Theileria-induced transformation, several host cell signaling pathways are activated that are involved in controlling parasite proliferation and survival, including the NF-kB, c-Jun N-terminal kinase (JNK) and c-Myc signaling pathways [1,[17][18][19], but the exact mechanism remains unclear. Decades of research has resulted in the identification of many parasite proteins that contribute to transformation, including TaPIN1 [20,21], TaSP [22,23] and Ta-p104 [24]. However, the molecules that play a key role in transformation remain unclear.…”
Section: Open Accessmentioning
confidence: 99%
“…This motif (T 131 PTK) is exposed to host cell cytosol and is only phosphorylated in interphase cells. Further experiments showed that TaSP interacts with CDK1 and drug inhibition of CDK1 altered the morphology of T. annulate ‐infected cells and caused a reduction in their proliferation, adding more evidence to the role of TaSP in transformation [Mackiewicz et al., 2020].…”
Section: Parasite Effectors At the Schizont Surfacementioning
confidence: 99%